O casal e a fonte de água: análise da narrativa mítica e sagrada - Barbosa, Michelle de Kássia Fonseca (2013)
In the Bible we see stories in the meeting of the wives of Isaac, Jacob and Moses, a mythic image, the same plot and a myth. This research aims to highlight and analyze these features seeking to understand them and respond to guiding question "What is the function and meaning of this narrative for the ancient Israelites?". Justify the search in the search for meaning of a sacred history of antiquity that inspired and instructed the people - Jews, and became so important that was recorded in its main holy book. From Mircea Eliade, Gilbert Durand, Joseph Campbell, Arnold Van Gennep, Gershom Sholem, among others, traveled a path where a reading is made of three Bible stories. The methodology used is that of literature with a qualitative approach with reference to the Hebrew Bible and books specializing in myth and symbol, watch out for an analysis supported by the anthropological school of religion. As results stand out: A scenario redundant - a couple who is in a well - alluding to a microcosm and refers the image center, as Eliade - the navel of the world as well, which draws the two complementary forces (male and female) that promote the creation, a plot that evolves into an outcome - an alien who presents after a long journey stops and rests in a well. A woman finds. There is a dialogue between them. There offering water. The woman returns to her home and reported the incident. The alien remains in the well. Relatives of the woman they meet abroad and invites him to join. The alien remains some time with them. Is a marriage; The myth of androgen as primary justification for marriage in Judaism; The journey in search of the bride; The symbolism of the meeting; The mitocrítica these Bible stories. In any way disregard the many other forms of analysis and interpretation previously promoted by researchers, theologians and biblical scholars. This is just a glimpse into the object of the meeting of the wives of the Biblical patriarchs. A look influenced by theorists of symbolic hermeneutics, giving its contribution to the understanding of something that is bigger than any one mind may have already guessed, is that the religious phenomenon and its various forms to submit to the man.